Konsep Keadilan Islam Pada Ranah Spesifik Poligami (Ta’adud Al-Zaujāt) Dalam Alquran Perspektif Mufassir Wahbah Al-Zuḥailī - Asmu’i, Asmu'i; Nasution, Muhammad Roihan; Harahap, Mardian Idris (Kamaya: Jurnal Ilmu Agama, 2024)
Issues surrounding polygamy in Islam are still a topic of debate among Islamic scholars and the Muslim community. Some of the main problems that are often discussed include the issue of justice which is the main requirement for polygamy. Especially in Indonesia, polygamy is a serious problem in family law, quite a few divorce problems are caused by polygamy. This research aims to explore the concept of Islamic justice in the specific realm of polygamy in the Koran and analyze Wahbah al-Zuḥailī's interpretation of the Koranic verse about justice in polygamy. This research uses qualitative methods with descriptive-analytic data analysis techniques. The results of this research show that in the Koran, polygamy is permitted and limited to four wives, provided that a husband must be able to act fairly. Meanwhile, in the Koran, the word adat is mentioned 28 times in 28 verses in 11 surahs. Furthermore, the concept of justice in polygamy according to Wahbah al-Zuḥailī's interpretation is justice in the material, not immaterial, sphere. Material justice means being fair in taking turns and being equal in providing material support to the wife. Immaterial justice is that which is related to matters of the heart, this justice is impossible to achieve by human ability.